INCLUSIVE COMPETENCE OF TEACHERS IN VOCATIONAL (VOCATION AND TECHNICAL EDUCATION) INSTITUTIONS AS A REQUIREMENT TODAY (Innovative professional education, 2023)
The rapid development of the inclusive form of education in the institutions of professional (vocational and technical) education in Ukraine indicates that the primary task and strategic goal of professional education is the formation of inclusive competence in teachers as a mandatory component of their profession. For the successful implementation of inclusive education against the background of intensive changes in differt of life professional education of Ukraine must optimize the transition to a new paradigm of education - an innovative one, according to which the preparation of teachers to implement the tasks of inclusive education must be based on competence principles. It was analyzed that an integral component of the inclusive competence of a teacher is the ability to use a wide range of innovative technologies and approaches to persons with special educational needs (SEN) in their professional and pedagogical activities.
Keywords: inclusive education, competences, inclusive competence, professional education